(Re) Visiting the concept of Managerial Skills in training the Administrator to work in MPE, EJ and Startup (Research, Society and Development, 2021)
The world of work has changed radically, and the emergence of challenges that seek from a future professional in administration the development of managerial skills to better serve the organizational development has become constant. However, for the student to perform well after training, characteristics that make up the competence itself are necessary. The objective of this study is to identify managerial competences in Micro and Small Enterprises (MPEs), Junior Enterprises (EJ) and Startups from a systematic study in SPELL and EnANPAD. A study with a systematic review approach was developed in which the results are treated with support in content analysis. According to the competences that are most competent in the studied works, categories were formed according to the demand for knowledge, skill and attitude that are stimulated in future administrators through experiential learning. Results show that the training experiences enable the learning and development of skills and the work in Micro and Small Junior Companies and Startups contribute to the development of skills, and the most emphatically affected were: delegation, conflict management, planning, flexibility, relationship and teamwork. Such skills contribute to employability, entrepreneurial spirit and professional success.